Prostate-specific membrane antigen for prostate cancer theranostics: from imaging to targeted therapy. Issue 3 (September 2018) - Arsenault, Frédéric; Beauregard, Jean-Mathieu; Pouliot, Frédéric
Abstract : Purpose of review: In recent years, major advances in molecular imaging of prostate cancers (PCa) were made with the development and clinical validation of highly accurate PET tracers to stage and restage the disease. Prostate-specific membrane antigen (PSMA) is a transmembrane protein highly expressed in PCa, and its expression has led to the development of PSMA-binding radiopharmaceuticals for molecular imaging or radioligand therapy (RLT). We herein review the recent literature published on diagnostic and therapeutic (i.e. theranostic) PSMA tracers. Recent findings: Development in small PSMA-targeted molecules labeled with gallium-68 and fluorine-18 show promising results for primary staging and detection of disease at biochemical recurrence using PET/computed tomography (PET/CT). Studies show a higher sensitivity and specificity, along with an improved detection rate over conventional imaging (CT scan and bone scan) or choline PET tracers, especially for restaging after prostate-specific antigen failure following loco-regional therapy. In addition, some PSMA tracers can be labeled with beta-minus and alpha particle emitters, yielding encouraging response rates and low toxicity, and potentially offering a new line of targeted therapy for metastatic castration-resistant PCa. Summary: PSMA-targeted tracers have shown unprecedented accuracy to stage and restage PCa using PET/CT. Given their specific biodistribution toward PCa tissue, PSMA RLT now offers new therapeutic possibilities to target metastatic PCa. Prospective multicenter randomized studies investigating the clinical impact of PSMA–targeted molecules are urgently needed.